2012
DOI: 10.1111/j.1365-3040.2012.02581.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pathogenic rhizobacteria interfere with the attraction of parasitoids to aphid‐induced plant volatiles via jasmonic acid signalling

Abstract: Beneficial soil-borne microbes, such as mycorrhizal fungi or rhizobacteria, can affect the interactions of plants with aboveground insects at several trophic levels. While the mechanisms of interactions with herbivorous insects, that is, the second trophic level, are starting to be understood, it remains unknown how plants mediate the interactions between soil microbes and carnivorous insects, that is, the third trophic level. Using Arabidopsis thaliana Col-0 and the aphid Myzus persicae, we evaluate here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 71 publications
7
132
1
1
Order By: Relevance
“…The compounds were expressed as percentages of peak areas relative to the internal standard (camphor) per 18 h of trapping using one plant. The volatiles of Arabidopsis were collected and analyzed as described previously (Pineda et al, 2013), with minor modification. Volatile trapping was done for 3 h at a flow of 300 mL/min, and the gas chromatography oven temperature program was as follows: 40°C for 2 min, raised at 10°C/min to 280°C, and then held for 4 min.…”
Section: Volatile Analysismentioning
confidence: 99%
“…The compounds were expressed as percentages of peak areas relative to the internal standard (camphor) per 18 h of trapping using one plant. The volatiles of Arabidopsis were collected and analyzed as described previously (Pineda et al, 2013), with minor modification. Volatile trapping was done for 3 h at a flow of 300 mL/min, and the gas chromatography oven temperature program was as follows: 40°C for 2 min, raised at 10°C/min to 280°C, and then held for 4 min.…”
Section: Volatile Analysismentioning
confidence: 99%
“…Leaf chemistry is a key component of many plant herbivore interactions and studies have found that soil microbes alter the leaf chemistry of their host plants (Meiners et al 2017). Pseudomonas fluorescens colonization induced systemic resistance in Arabidopsis, which significantly reduced the growth of the herbivore S. exigua, but it also changed the composition of volatiles induced by the generalist aphid, Myzus persicae, making the plant less attractive to the aphids' natural enemies (Van Oosten et al 2008;Pineda et al 2013;Sugio et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We have focused on aboveground plant vegetative tissues because most information on community processes is available for insect communities associated with vegetative plant shoots. However, similar systemic effects are expected when including the belowground tissues (Soler et al, 2013). Including belowground interactions will be important, even when it further increases the complexity of the interactions and therefore the difficulty of understanding the effects of a phenotypically plastic plant on the development of the associated community.…”
Section: Future Perspectivesmentioning
confidence: 87%
“…Herbivorous insects are connected by both local and systemic plant-mediated interactions. Systemic effects may involve both roots and shoots (Soler et al, 2013) or leaves and flowers (Kessler et al, 2011;Lucas-Barbosa et al, 2011). We have focused on aboveground plant vegetative tissues because most information on community processes is available for insect communities associated with vegetative plant shoots.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation